Hubungan Faktor Psikososial Terhadap Kejadian Kecelakaan Kerja Pada Pekerja PT X Kabupaten Kampar - yuharika pratiwi; Retno Putri; Tessa Harianti Sidik (LPPM Universitas Abdurrab, 2023)
Occupational accidents are unexpected events, without intentional elements, causing workers to be in danger, cause disrupting work activities, and resulting in losses, injuries, illnesses, and damages. The International Labor Organization (ILO) reports that 2.3 million people die each year cause of work accidents. Indonesia is in the fifth rank of deaths due to work accidents in Southeast Asia. Occupational accidents in the industrial sector are in second place. Many factors cause work accidents, one of which is psychosocial factors. Palm Oil Mill PT. X is an industrial company engaged in the processing of palm oil. Workers come into contact with chemicals and are associated with stressors in the social environment of the workplace that can trigger work accidents. The initial surveys were conducted on 30 workers at PKS PT. X obtained 90% of work accidents. This study used an analytic observational design, with a cross-sectional study design. The study aimed to determine the relationship between psychosocial factors and the incidence of work accidents among workers in the laboratory and PKS processing departments of PT. X. The results of the Pearson correlation test found that there was a relationship between psychosocial factors and the occurrence of work accidents in laboratory and processing workers at PT. X, Kampar Regency.